The American way of postwar: post-World War II occupation planning and implementation - Hudson, Walter M. (Kansas State University, 2010)
The United States Army became the dominant U.S. government agency for post-World War II occupation planning. Despite President Roosevelt’s own misgivings, shared by several influential members of his Cabinet, the Army nonetheless prevailed in shaping occupation policy in accordance with its understanding and priorities. The Army’s primacy resulted from its own cultural and organizational imperatives, to include its drive towards professionalization and its acceptance of legalized standards for conflict in the nineteenth and early twentieth centuries. Other related factors included the Army’s ability to create coherent internal doctrine, the training and experience of its leaders, the relative weakness of comparative civilian agencies, the real-world experiences of civil affairs in North Africa in 1942-43, and the personality and leadership style of President Roosevelt himself. As a result, the Army created internal training and education, doctrine, and organizations that operated both at the strategic and tactical level to implement military government in accordance with the Army’s institutional understanding. The Army’s planning and implementation of military government in Germany, Austria, and Korea show the effects of the Army’s dominance in planning and implementing the postwar occupations. Furthermore, in these three occupations (unlike Japan’s), of particular concern were how the Americans interacted with their Soviet counterparts in the occupied territories at the beginning of the Cold War. As these three occupations reveal, American military government in those locations, as well as the actions of the occupants themselves, profoundly shaped American interests in those countries and thus profoundly shaped American policy during the early Cold War.
Keywords: occupation; military government; World War II; U.S. Army; planning; Cold War; History, United States (0337)